The impact of stereotype threat on endogenous poverty-elimination dynamics in generationally poor individuals - Wu, Na; Fu, Anguo; Liu, Yangxiong; Yue, Tong; Li, Jibo; Wang, Xiaogang; Huang, Xiting (Frontiers in Psychology, 2023)
Introduction. The study examines the impact of stereotype threat on generationally poor individuals and its effect on endogenous poverty-elimination dynamics. It also explores the extent to which self-affirmation has an intervention effect on the negative impact of stereotype threat. Methods and Results. In Study 1, statements that contained negative stereotypes were used to elicit stereotype threat in generationally poor individuals; the results show that stereotype threat reduced the performance of generationally poor individuals in a mental-rotation task. Study 2 used a questionnaire to measure the endogenous dynamics of generationally poor individuals attempting to escape poverty after experiencing stereotype threat; participants in the stereotype-threat group showed lower-level endogenous poverty-elimination dynamics than those in the control group. In Study 3, a self-affirmation intervention was administered to the stereotype-threat group after the stereotype threat was induced. Participants in the self-affirmation group were shown to have higher-level endogenous poverty-elimination dynamics than those in the control group. Discussion. These findings confirm the negative effect of stereotype threat on endogenous poverty-elimination dynamics and verify the effectiveness of self-affirmation in mitigating the negative effects of stereotype threat.